Seismic response of monopile supported offshore wind turbine in liquefiable soil. (June 2021) - Patra, Sangeet Kumar; Haldar, Sumanta
Abstract: Offshore wind turbines (OWT) are now constructed in the seismically active regions due to rising energy demand. This study investigates the seismic response of the monopile supported OWT in liquefiable sand deposits under combined operational and seismic loads. A coupled soil-monopile-tower interaction model is developed in OpenSees . Monopile and tower are modelled as linear Euler – Bernoulli beam. Monopile-soil interaction is modelled using nonlinear p-y spring. Free-field motion at the outer spring nodes due to seismic motion is simulated by modelling a soil domain using a two-dimensional plane strain quadrilateral element considering a with a solid–fluid fully coupled model. Various historical strong motion records and spectrum consistent artificial strong motion data are scaled and applied on OWT structure and various operational loads on the structure. The effect of intensity, sustained maximum acceleration of earthquake, and depth of liquefaction on the dynamic response of the OWT structure is studied. A design implication is also suggested for the OWT structure in liquefiable soil.